Preventive Legal Education as a Strategy for Empowering Women Victims of Domestic Violence (KDRT) in Accessing Legal and Psychological Services - Karina, Ica; Wibowo Gumbira, Seno; Ginting, Grenaldo; Umar, Nurifana; Pratiwi Puwa, Suryani Intan (Jurnal Smart Hukum (JSH), 2026)
This article examines preventive legal education as a strategic mechanism for empowering women victims of domestic violence (Kekerasan Dalam Rumah Tangga/KDRT) in Indonesia, specifically focusing on their access to integrated legal and psychological services. Using qualitative phenomenological methodology through in-depth interviews and thematic analysis, this study explores how targeted legal awareness programs strengthen victim agency in navigating justice systems and psychological support mechanisms. The research involved interviews with 18 participants comprising female KDRT victims, legal aid providers, psychological counselors, and community advocates across three Indonesian provinces. Findings reveal that comprehensive legal education programs significantly enhance victim empowerment by demystifying legal processes, clarifying rights under Law Number 23 of 2004, and facilitating timely access to protective services. The implementation of preventive legal education demonstrates capacity to transform victim consciousness, shifting perspectives from self-blame to recognition of legal rights and entitlements. Participants reported increased willingness to report incidents after legal awareness interventions, with 72.2% of victims subsequently accessing formal legal assistance compared to 22.8% prior to education programs. The study identifies critical success factors including integration of psychological support with legal education, community-based delivery mechanisms, and trauma-informed facilitation approaches. However, significant barriers persist, including cultural stigma, limited accessibility in rural areas, and insufficient institutional capacity. This research contributes to evidence-based advocacy for mainstreaming preventive legal education within comprehensive victim support ecosystems in Indonesia, proposing a holistic empowerment model combining legal literacy, psychological recovery, and community mobilization to achieve sustainable gender justice.